A Dél-Dunántúl a piacgazdasági átmenetben - Nemes Nagy, József (Tér és Társadalom, 1994)
The large region covering four counties (Baranya, Somogy, Tolna, Zala) concentrates about one tenth of the Hungarian economic potential. According to indexes that reflect the economic situation the region has a economic state comparible with the national average in the early 1990s. Its situation is much more favourable than that of the Eastern and Northern part of the country, but less favourable than that of North Transdanubia and the central region, including Budapest. This position is justified by many economic indices: division of new enterprises, joint ventures and their economic indices, taxable earnings, unemployment form the base of analysis. By all these, through factor-analysis we can show the presence of both economic modernisational tendencies and of the traditional economic structure. In South Transdanubia we can find small regions with totally different economic characters. County seats emerge in all the counties in matters of economic strength, this is especially true of Pécs, the most important centre of the region, a zone clearly specialised for tourism, besides Lake Balaton. The agrarian regions with many tiny villages are also dominant. The region has a special economic "enclave", Paks, where the only Hungarian nuclear power station was sited. The Mecsek Hills coal mining (Komló) shows features of features. The long term regional development concept of South Transdanubia would be made up from the concepts of the specific small regions. The region cannot rely on a substantial central state support in the future, either, and this give the local initiatives and innovation the most important role.